The Methods of Communicative Culture in The Process of Teaching the English Language on The Example of Technical Direction Students at Non-Philological Universities - Mukhamedjanova Sitorabegim Djamolitdinovna (Genius Journals, 2022)
This article describes the recommendation of interactive methods of preparing the English language for professional activity in the development of the communicative culture of future specialists in higher education.
Keywords: Communicative culture; interactivity; future specialists; interactive methods